The user acceptance of an agricultural e-commerce platform for women in underserved rural areas - Mahure, Hlobisile (Department of Computer Science, 2025)
Problem Statement: Agricultural e-commerce technologies have the potential to empower farmers in rural areas. These platforms can help agriculturalists by enhancing market access, reducing reliance on intermediaries, increasing sales, providing access to modern technologies, and ultimately leading to genuine economic independence. Despite their potential benefits, current e-commerce platforms remain underutilized by rural farmers, particularly women. The acceptance of these solutions is often hindered by a myriad of factors such as lack of relevance to users' needs, language barriers, infrastructure issues, digital illiteracy, economic barriers, and socio-cultural constraints. This highlights the need for further research to investigate user acceptance of agricultural e-commerce among women. Understanding user acceptance can help identify obstacles and develop strategies for digital inclusion, which is an area that remains understudied in rural settings. Existing literature often falls short of addressing the specific needs and challenges of female farmers in rural areas, overlooking factors such as language, design, and preferences that resonate with this demographic, thus leaving these women underserved. Purpose of the study: The primary aim of this study was to assess the user acceptance of an agriculture e-commerce platform designed to support female farmers in underserved rural areas. Research Methodology: The research utilized a convergent parallel mixed-method approach, involving both qualitative and quantitative methods. The study area chosen was Jeppes Reef, a small rural community renowned for its agricultural activities. Thirty participants were selected using snowball sampling, convenience sampling, simple random sampling, and purposive sampling. A structured Survey was administered to twenty female farmers between the ages of 18 and 65. Semi-structured interviews were conducted with five female farmers and five specialists to assess the user acceptance of the platform. The questions of the data collection instruments were based on technology acceptance constructs of perceived usefulness, perceived ease of use, attitude toward using, and behavioral intention to continue using the platform. Findings: The agricultural e-commerce was well received, with most participants acknowledging its value (Perceived Usefulness) and expressing the intent (Behavioral intention) to use the platform after their suggested improvements were implemented. Furthermore, most participants found the application easy to use (Perceived Ease of Use) and had a positive attitude toward using (Attitude Toward Using) the platform. However, the research identified underlying technical and external factors that hindered widespread user acceptance. These included issues such as accessibility for individuals with disabilities, a difficult user experience for the elderly, and the lack of inclusion of other South African local languages on the platform. External factors such as internet connectivity challenges, limited access to smart devices, digital illiteracy, and expensive data were also found to impede user interaction and engagement with the application. Benefits of the study: This research provides important insights for software developers, governments, policymakers, and organizations interested in establishing agricultural e-commerce platforms for women in rural areas. It offers a detailed guide for designing and developing applications tailored to the needs of the intended users and gaining wider user acceptance. Furthermore, the research contributes to the current body of knowledge on the Technology Acceptance Model, offering detailed guidance on its application in various contexts, including gender-based and rural-specific contexts, to measure user acceptance. Overall, the research offers comprehensive guidelines for creating an all-encompassing agricultural e-commerce platform designed to empower women in underserved rural areas.